Neoadjuvant nivolumab with chemotherapy: a miraculous new regime in treatment of resectable lung cancers - Babar, Nisha; Syeda Zuha Hasan; Samra Rabbani (Journal of the Pakistan Medical Association, 2022)
Madam, lung cancer is one of the commonly diagnosed causes of cancer mortality and morbidity worldwide, accounting for approximately 1.76 million deaths annually.1 In the past overall survival in patients with non-small cell lung cancer (NSCLC) remained uncertain. Many treatment regimens were under trial2 until, a breakthrough study incorporating neoadjuvant nivolumab with chemotherapy showed tremendous success in phase 3 CheckMate 816 trail3. Moreover, the FDA has recently approved this therapy for early-stage NSCLC.4 Nivolumab is an anti–programmed death 1 (PD-1) human antibody, which restores antitumor T cells activity. Whereas platinum-doublet chemotherapy improves antitumor immunity.3 In this trail, approximately 350 patients were randomly assigned in an equal ratio to receive nivolumab (360 mg) plus chemotherapy or chemotherapy alone for consecutive 3 weeks for three cycles before surgery. Two primary end points were established, event-free survival and complete pathological response. Median event-free survival was 31.6 months with nivolumab plus chemotherapy compared to 20.8 months with chemotherapy alone (hazard ratio for disease progression, recurrence, or death, 0.63; P=0.005). The pathological complete response was 24.0% in the nivolumab plus chemotherapy group and 2.2% in chemotherapy alone group (odds ratio, 13.94; P<0.001). Also, no surgery-related adverse events were observed with the addition of nivolumab to neoadjuvant chemotherapy.3 It concludes that nivolumab with chemotherapy showed promising results than chemotherapy alone in patients with resectable NSCLC. However, stage IIIA patients were majorly benefited than stage IB or II patients.3 Therefore, it is imperative that more clinical trials must be conducted to obtain maximum benefit at all possible stages and a proper follow up for data is needed to draw better conclusions.